THE IMPACT OF DIGITAL FINANCIAL DEVELOPMENT ON COMMERCIAL BANK STABILITY (Contemporary Journal of Social Science Review, 2025)
This study explores the relationship between digital financial development and the stability of commercial banks, focusing on how technological advancements and operational efficiency shape resilience in the financial sector. Using a dataset of 1,000 observations, the analysis examines pointers such as mobile banking usage, internet transfers, digital payments, and cost efficiency, while controlling for regional effects. The findings reveal that digital payments and operational efficiency pointedly boost bank stability, with efficiency emerging as the strongest determinant of resilience. In contrast, mobile banking adoption and internet transfers show positive but statistically insignificant effects, suggesting that their stabilizing role is still developing. Regional differences negatively impact steadiness, highlighting the importance of institutional and structural contexts. Furthermore, investigative tests confirm the presence of heteroskedasticity, indicating that mistake modification is thoroughly influenced by digital and regional factors. Overall, the learning concludes that while DFD supports financial stability, its assistances are unequally dispersed and extremely dependent on effectiveness, regulation, and regional readiness. The results underline the need for helpful rules, digital substructure investments, and financial literacy initiatives to maximize the possible of digital finance in promoting a stable and inclusive banking system.